1999
DOI: 10.1007/pl00006803
|View full text |Cite
|
Sign up to set email alerts
|

Transient Production of Formate During Chemolithotrophic Growth of Anaerobic Microorganisms on Hydrogen

Abstract: The homoacetogenic bacteria Acetobacterium woodii, A. carbinolicum, Sporomusa ovata, and Eubacterium limosum, the methanogenic archaeon Methanobacterium formicicum, and the sulfatereducing bacterium Desulfotomaculum orientis all produced formate as an intermediate when they were growing chemolithoautotrophically with H 2 and CO 2 as sources of energy, electrons, and carbon. The sulfate-reducing bacterium Desulfovibrio vulgaris grew chemolithoheterotrophically with H 2 and CO 2 using acetate as carbon source, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…Formate is an alternative electron donor for hydrogenotrophic methanogens [64] and a former study showed formate synthesis from H 2 /CO 2 by bacteria [65]. Furthermore, pure cultures of hydrogenotrophic methanogens (Methanobacterium formicicum) or acetogenic bacteria transiently produced formate during H 2 /CO 2 metabolism [66,67]. Hence, it can be inferred that homoacetogens, SAOB and hydrogenotrophic methanogens could have contributed to concomitant formate formation, along with methanogenesis.…”
Section: Effect Of Medium Compositionmentioning
confidence: 99%
“…Formate is an alternative electron donor for hydrogenotrophic methanogens [64] and a former study showed formate synthesis from H 2 /CO 2 by bacteria [65]. Furthermore, pure cultures of hydrogenotrophic methanogens (Methanobacterium formicicum) or acetogenic bacteria transiently produced formate during H 2 /CO 2 metabolism [66,67]. Hence, it can be inferred that homoacetogens, SAOB and hydrogenotrophic methanogens could have contributed to concomitant formate formation, along with methanogenesis.…”
Section: Effect Of Medium Compositionmentioning
confidence: 99%
“…Reduction of formate, an intermediate of the CO 2 reduction in the methyl branch of the reductive acetyl‐CoA pathway, takes four more reduction equivalents and one mol ATP. Thus formate accumulation indicates a disturbance of the reductive acetyl‐CoA pathway as it was observed for other acetogens, for example, Acetobacterium woodii , Sporomusa ovata , or Acetobacterium wieringae in acetogenic bacteria (Diekert & Wohlfarth, ; Groher & Weuster‐Botz, ; Kantzow & Weuster‐Botz, ; Mayer & Weuster‐Botz, ; Peters, Janssen, & Conrad, ). Strong initial formate accumulation occurred basically at p CO,in = 200 mbar but not at p CO,in = 500 mbar.…”
Section: Resultsmentioning
confidence: 64%
“…Strain F1 can generate formate and a small amount of acetate from consumption of H 2 and CO 2 . Generation of formate from H 2 /CO 2 by Desulfovibrio strains has been reported previously (Peters et al 1999), but only chemolithoheterotrophically (i.e., with acetate as fixed carbon source). It was suggested that possessing a formate dehydrogenase is the prerequisite for producing formate during chemolithotrophic growth on H 2 (Peters et al 1999).…”
Section: Discussionmentioning
confidence: 71%
“…strain G11 was claimed to be an autotroph, but no supporting experimental data were presented (McInerney et al 1981;Dolfing et al 2008). Mixotrophic growth with H 2 /CO 2 and acetate is more common with Desulfovibrio bacteria, e.g., D. desulfuricans (Londry and Marais 2003;Mechalas and Rittenberg 1960) and D. vulgaris (Peters et al 1999). Notably, formate was formed as an intermediate when D. vulgaris was grown chemolithoheterotrophically with H 2 /CO 2 and acetate under sulfate-limiting conditions (Peters et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation